Measurements of normal joint angles by goniometry in calves - Şirin, Ö Şengöz; Çelik, M. Timuçin; Özmen, A.; Avki, S. (Veterinary and Comparative Orthopaedics and Traumatology, 2014)
The aim of this study was to establish normal reference values of the forelimb and hindlimb joint angles in normal Holstein calves.Thirty clinically normal Holstein calves that were free of any detectable musculoskeletal abnormalities were included in the study. A standard transparent plastic goniometer was used to measure maximum flexion, maximum extension, and range-of-motion of the shoulder, elbow, carpal, hip, stifle, and tarsal joints. The goniometric measurements were done on awake calves that were positioned in lateral recumbency. The goniometric values were measured and recorded by two independent investigators.As a result of the study it was concluded that goniometric values obtained from awake calves in lateral recumbency were found to be highly consistent and accurate between investigators (p <0.05).The data of this study acquired objective and useful information on the normal forelimb and hindlimb joint angles in normal Holstein calves. Further studies can be done to predict detailed goniometric values from different diseases and compare them.
Keywords: Calf; joint angle; range-of-motion; goniometry